Preparation and Properties of Long Afterglow CaAl2O4 Phosphors Activated by Rare Earth Metal Ions - Wako, Ali Halake (University of the Free State Republic of South Africa, 2011)
This work comprises of several aspects of calcium-aluminate phosphor activated with rare earth metal ions i.e. (CaAl2O4:Eu2+, Nd3+, and Dy3+). In particular the luminescent and structural properties of the long afterglow CaAl2O4:Eu2+,Nd3+,Dy3+ phosphors prepared by urea-nitrate solution-combustion method were investigated. The solution-combustion method is more efficient because phosphors with high efficiency were obtained at low temperature (500 oC) in a very short period of time (5 min). The effects of varying concentration of host matrix composition (Ca:Al), flux i.e. boric acid (H3BO3), activator (Eu2+) and co-activator (Nd3+/Dy3+) mass ratios and urea ((NH2)2CO) on the structural, luminescent, and thermoluminescent(TL) properties of the CaAl2O4:Eu2+, Nd3+, Dy3+ phosphors were studied. It was observed that Ca:Al mass ratios greatly affect the crystalline structure of the material. The results of the X-ray diffraction (XRD) analysis reveal that the formation of several crystalline phases depends on the ratios of the host material. The XRD peaks show the presence of other phases such as Ca3Al2O6 and CaAl4O7 but the predominant phase formed was that of CaAl2O4. However it was found that the crystalline structure is generally not affected by the variation of the co-dopants concentration. Photoluminescence (PL) studies revealed a general rise in intensity with an increase in the mass ratio of Ca:Al. The highest PL intensity was observed with 0.7% Ca. The luminescent intensities vary from each other when co-doped with various proportions of Nd3+ and Dy3+. The addition of H3BO3 favored the formation of pure monoclinic CaAl2O4 phase while the variation of the amount of ((NH2)2CO) showed mixed phases although still predominantly monoclinic. Both boric acid and urea to some extent influence the luminescence intensity of the obtained phosphor but unlike the case of CO(NH2), the emission peak for H3BO3, does not shift evidently because the energy level difference of 4f-5d does not change obviously. The broad blue emissions consisting mainly of symmetrical bands having maxima between 440–445 nm originate from the energy transitions between the ground state (4f7) and the excited state (4f65d1) of Eu2+ ions while the narrow emissions in the red region 600-630 nm arise from the f-f transitions of the remnant unreduced Eu3+ions. High concentrations of H3BO3 generally reduce both intensity and lifetime of the phosphor powders. The optimized content of H3BO3 is 5.8 mol % for the obtained phosphor with excellent properties. XRD analysis of the influence of Eu2+ and Nd3+ doping concentrations on the morphological, structural and PL properties of the CaAl2O4: Eu2+; Nd3+ phosphor, depict a dominant monoclinic phase that indicates no change in the crystalline structure of the phosphor even with high concentration of Eu2+ or Nd3+. The Energy Dispersive x-ray Spectroscopy (EDS) and Fourier Transform Infra-Red Spectroscopy (FTIR) spectra showed the expected chemical components of the phosphor. The excitation iv spectra show one broadband from 200 nm to 300 nm centered around 240 nm corresponding to the crystal field splitting of the Eu2+ d-orbital. The prepared phosphor compositions exhibit PL emission in the blue region with a maximum around 440 nm. This is a strong indication that there was dominantly one luminescence centre, Eu2+ which represents emission from transitions between 4f7 (8S7/2) ground state and the 4f6-5d1 excited state configuration. Two other, minor peaks, at 580 and 614 nm indicate the presence of remnants of Eu3+ ions as a result of incomplete reduction during sample preparation. High concentrations of Eu2+ and Nd3+ generally reduce both intensity and lifetime of the phosphor powders. The optimized content of Eu2+ is 0.36 mol % and for Nd3+ is 0.09 mol % for the obtained phosphors with good properties. The decay characteristics exhibit a significant rise in initial intensity with increasing Eu2+ doping concentration while the decay time increased with Nd3+ co-doping. Analysis of the TL glow curves is one of the most significant ways to measure the number of traps and also the activation energy of the trap levels in luminescent materials. In the present study TL properties of the CaAl2O4:Eu2+, Nd3+,Dy3+ phosphors were investigated above room temperature by use of Nucleonix 1009I TL reader. The trap depths were estimated with the aid of the peak shape method. The glow curve of CaAl2O4:Eu2+ with a first peak at 50 °C was found to correspond to several traps. The ratio of Nd3+:Dy3+ ions were observed to influence the position, concentration and type of traps formed. The observed afterglow can be ascribed to the generation of suitable traps due to the presence of the Nd3+ trap levels. Trivalent rare earth ions (Nd3+/Dy3+) are thought to play the role of hole traps in calcium aluminate phosphors (CaAl2O4:Eu2+). In these phosphors, Eu2+ ions act as luminescent centre emitting in the blue (λ max = 440 nm) region. Despite a large number of research on the phenomenon the mechanism of the persistent luminescence of CaAl2O4:Eu2+,Nd3+,Dy3+ has not been well presented. A proper understanding of the exact luminescence mechanisms and the identification of trap levels or locations in long phosphorescent materials is required for their use in areas such as detection of radiation, sensors for cracks in buildings, fracture of materials and temperature among others.
A Thesis Presented in Fulfillment of the Requirements for the Degree of Magister Scientiae / Master of Science (M.Sc) In the Faculty of Natural and Agricultural Sciences, Department of Physics At the University of the Free State Republic of South Africa
Keywords: CaAl2O4: Eu2+; Dy3+; Nd3+; Solution – Combustion Method; Morphology; Excitation; Band gap; Luminescence; Rare Earth Ions; traps levels; decay time; long afterglow